Alcohol consumption in 0.5 million people from 10 diverse regions of China: prevalence, patterns and socio-demographic and health-related correlates. - Millwood, I; Li, L; Smith, M; Guo, Y; Yang, L; Bian, Z; Lewington, S; Whitlock, G; Sherliker, P; Collins, R; Chen, J; Peto, R; et al. (Oxford University Press, 2013)
BACKGROUND: Drinking alcohol has a long tradition in Chinese culture. However, data on the prevalence and patterns of alcohol consumption in China, and its main correlates, are limited. METHODS: During 2004-08 the China Kadoorie Biobank recruited 512,891 men and women aged 30-79 years from 10 urban and rural areas of China. Detailed information on alcohol consumption was collected using a standardized questionnaire, and related to socio-demographic, physical and behavioural characteristics in men and women separately. RESULTS: Overall, 76% of men and 36% of women reported drinking some alcohol during the past 12 months, with 33% of men and 2% of women drinking at least weekly; the prevalence of weekly drinking in men varied from 7% to 51% across the 10 study areas. Mean consumption was 286 g/week and was higher in those with less education. Most weekly drinkers habitually drank spirits, although this varied by area, and beer consumption was highest among younger drinkers; 37% of male weekly drinkers (12% of all men) reported weekly heavy drinking episodes, with the prevalence highest in younger men. Drinking alcohol was positively correlated with regular smoking, blood pressure and heart rate. Among male weekly drinkers, each 20 g/day alcohol consumed was associated with 2 mmHg higher systolic blood pressure. Potential indicators of problem drinking were reported by 24% of male weekly drinkers. CONCLUSION: The prevalence and patterns of drinking in China differ greatly by age, sex and geographical region. Alcohol consumption is associated with a number of unfavourable health behaviours and characteristics.